2007
DOI: 10.1080/03650340701571033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic manures and fertilizers on organic matter and nutrients status of the soil

Abstract: A long-term field demonstration was initiated in 1995 to evaluate the effect of organic manures (FYM, poultry manure and pressmud) and mineral fertilizers on changes of pH, electrical conductivity (EC), organic C and nutrient contents under pearl millet -wheat cropping sequence. Continuous application of organic manures alone or in conjunction with NP fertilizer for 10 years decreased the soil pH. However, a reverse trend was observed in case of EC. Organic C content of the soil decreased from its initial valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 8 publications
12
41
2
Order By: Relevance
“…in sewage sludge. Antil & Singh [5] also reported that different organic manures were found to be loaded with OC, TKN, PO 4 3-and K + and their application significantly increased the nutrients and enhance the soil fertility. Therefore, all the treatments used in the present study were found to be loaded with plant nutrients and may enhance the soil fertility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in sewage sludge. Antil & Singh [5] also reported that different organic manures were found to be loaded with OC, TKN, PO 4 3-and K + and their application significantly increased the nutrients and enhance the soil fertility. Therefore, all the treatments used in the present study were found to be loaded with plant nutrients and may enhance the soil fertility.…”
Section: Resultsmentioning
confidence: 99%
“…Agriculture remains a soil-based industry, there is no way that required yield increases of the major crops can be attained without ensuring that plants have an adequate and balanced supply of nutrients [5][6][7]. The appropriate environment must exist for nutrients to be available to a particular crop in the right form, in the correct absolute and relative amounts, and at the right time for high yields to be realized in the short and long term [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Antil and Singh [69] also reported that the application of organic manures, such as cow or poultry manure, in conjunction with mineral fertilizer was very effective in sustaining crop productivity. Moreover, the integrated use of organic and inorganic fertilizers also has environmental benefits, as it reduces both chemical fertilizer usage and N losses, and allows for sustainable crop production [70].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, only CM application might not produce an optimal rice yield. Recently, many researchers including [23] [24] and [25] indicated that use of organic manures in conjunction with mineral fertilizer is very important for ensuring better soil health and sustaining crop productivity. Therefore, a mix application of manures with mineral N fertilizer might provide high inorganic N in soil and higher crop production.…”
Section: Grain Yieldmentioning
confidence: 99%